A reversible turn-off fluorescence probe (HNAPP) for Zn(ii) ion and inorganic phosphate ions (H2P and HP) at physiological pH1. Issue 67 (24th July 2015) - Hens, Amar
<x xml:space="preserve">Abstract</x> NOO coordinating tritadentate zinc sensor (λex = 400 nm, λem = 492 nm, ϕF = 0.45) act as a highly selective sensor for inorganic phosphate (HP/H2P) by ON–OFF signaling at physiological pH.